Stress levels experienced by parents of children with and without attention-deficit/hyperactivity disorder during the back-to-school period: results of a European and Canadian survey. (March 2015) - Hernández-Otero, Isabel; Doddamani, Lakshman; Dutray, Benoit; Gagliano, Antonella; Haertling, Fabian; Bloomfield, Ralph; Ramnath, Gracita
Abstract Objective. The back-to-school stress survey was designed to compare stress in parents of children/ adolescents with/without attention-deficit/hyperactivity disorder (ADHD) in six European countries and Canada when children prepare to return to school. Methods. Parents of children/adolescents (6–17 years) with/without ADHD were recruited and interviewed by a consumer research organization. Parents rated potentially stress-causing situations (both standard and specifically related to the return to school) on a scale from 1 (low stress) to 10 (high stress). Mean scores were compared using Student's t-test. Results. In Europe, 613/693 (mean [SD] age: 40.7 [7.0]/40.1 [6.9] years) and in Canada, 102/150 (mean [SD] age: 44.4 [8.1]/44.1 [7.2] years) parents of children with/without ADHD, respectively, participated in the survey. Children with ADHD (mean [SD] age: 11.2 [3.2]/12.6 [3.2] years in Europe/Canada) had generally similar characteristics in both samples. Parents in the ADHD group showed higher stress levels than parents in the non-ADHD group in all situations (p < 0.001 for Europe). The return to school was considered one of the most stressful events during the year. Conclusions. In Europe and Canada, ADHD has a significant impact on parental stress, particularly during the back-to-school period. This can have important implications as parental stress can affect presentation of ADHD symptoms.